Early and late postoperative complications of robot-assisted radical subcutaneous mastectomy with endoprosthesis - G. E. Kvetenadze; E. V. Shivilov; Kh. S. Arslanov; L. G. Zhukova; I. E. Khatkov (Опухоли женской репродуктивной системы, 2022)
Over the past two decades, the surgical treatment of breast cancer (BC) has changed from standard radical mastectomies to organ-preserving and reconstructive plastic surgeries using endovideosurgical and robotic technologies.  Robot-assisted radical subcutaneous mastectomy, as a minimally invasive method of surgical treatment  of BC in the early stages, is recognized as safe and effective.The results of robot-assisted radical subcutaneous mastectomy and radical subcutaneous mastectomy with endoprosthesis in 27 patients with histologically verified BC are presented. A comparative assessment of postoperative complications of robot-assisted radical subcutaneous mastectomy with endoprosthesis and radical subcutaneous mastectomy with endoprosthesis was performed. It was found that the postoperative period in robotic interventions is more favorable, which confirms the low need for analgesics, the absence of signs of the formation of hematomas of the surgical wound, as well as a decrease in the frequency of inflammatory infiltrates and gray soft tissues in the area of the postoperative suture. Performing a robot-assisted radical subcutaneous mastectomy with endoprosthesis can significantly improve the surgical and aesthetic results of BC treatment in the early stages of this disease.